Optimalisasi Integrated Digital Marketing Untuk Meningkatkan Daya Saing Umkm Desa Balleanging - Nur Fadilah Ayu Sandira; Chalid Imran Musa; Azlan Azhari; Nulthazam Sarah; Kristina Parinsi (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service activity aimed to strengthen the competitiveness of micro, small, and medium enterprises in Balleanging Village, Bulukumba Regency, through the optimization of integrated digital marketing. Using a participatory educational approach, the program combined an opening session, a Focus Group Discussion to map partners' needs, presentation of material on integrated digital marketing strategy, and a mentoring session addressing participants' specific concerns. Materials covered market segmentation and customer persona development, integration of digital channels such as Instagram, TikTok, marketplace, and WhatsApp Business, marketplace optimization, engagement-based content strategy, and basic data analytics literacy. The results show that participants gained a clearer understanding of structured digital marketing planning and greater enthusiasm to integrate their promotional channels. This activity demonstrates that participatory mentoring can help rural MSMEs shift from fragmented digital promotion toward a more integrated marketing system that supports sustainable local economic competitiveness